An investigation of the effectiveness of using analogies in teaching and learning scientific concepts - Ballard, Florence Nesamony (Curtin University, 2011)
Educators are constantly looking for effective teaching strategies, which can engender a favourable conceptual change in students within a constructivist paradigm. Teaching science with analogy could be one of such instructional strategies found effective in motivating students by providing them with familiar and tangible visual stimuli taken from the students‘ world to provide a basis for bridging and promoting associations between a known and an unknown realm. In this way, a complex, abstract concept can be made simple and interesting by reducing or eliminating students‘ misconceptions and alternative frameworks. This study was undertaken to find out whether a systematically planned and presented analogy using the FAR Guide has the capacity to enhance student understanding, remove misconceptions and improve higher order thinking. The sample consisted of 154 students from a state high school in Queensland, Australia, which caters for learners coming from 50 different ethnic groups settled in Australia. Five different analogies were presented to students in grades 8, 11 and 12, aged 12-18 years, as a component of their science, chemistry and biology lessons, respectively. This cohort consisted of 76 boys and 78 girls and the effectiveness of these analogies was studied by collecting qualitative and quantitative data. The five chosen analogies were designed cautiously to eliminate and minimise any discrepancy or ambiguity between the analog and target.All had qualities, which were appealing to the students. They were deliberately made to appear different from the regular 'chalk and talk‘ method and all the visuals were made colourful and attractive with appropriate titles, labels and short notes; thus gaining maximum attention to perceive the analog-target relationship. Two examples relating to real life situations, an outdoor-game, a cut and paste paper craft activity and a partly animated Power Point presentation were presented as analogies. The diagnostic instruments were carefully structured so that the multiple choices would readily bring out the understanding of the concept and misconceptions held by the students, both prior to and after the presentation of the analogies. The pretest results were not revealed to the students until the posttest was completed and evaluated. This research followed specific stages in addressing the research questions and did not predetermine or delimit the direction the investigation took in its course. A paired samples t-test conducted to evaluate the impact of the instruction showed a statistically significant increase in the scores from the pretest to posttest, indicating improved understanding, an increase in higher order thinking and a considerable decrease in misconceptions and alternative frameworks.